Pakaian Adat Tradisional Daerah Propinsi Sulawesi Tenggara / Husein A. Chalik, dkk. ; editor, Djohan Mekuo, Djuharta Meronda - Husein A. Chalik; Hazirun; La Ode Ibu; Hasanuddin; Djohan Mekuo; Djuharta Meronda ([s.n])
vii, 129 hlm. : ilus. ; 23 cm.